2020
DOI: 10.5603/ep.a2020.0038
|View full text |Cite
|
Sign up to set email alerts
|

Low serum levels of meteorin-like/subfatin: an indicator of diabetes mellitus and insulin resistance?

Abstract: Introduction: Meteorin-like (Metrnl), also known as subfatin, is a recently discovered adipokine with a favourable effect on insulin sensitivity. Studies have shown lower Metrnl levels in obese patients. However, data on its circulating levels in type 2 diabetes mellitus (T2DM) patients are contradictory. This study aims to evaluate serum Metrnl levels in T2DM patients and determine the relationship between serum Metrnl levels and insulin resistance in these patients. Material and methods: This cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
5
10
0
Order By: Relevance
“…Article Thieme ic individuals [19]. Other studies reported lower METRNL concentration in patients with T2D with a gradual decrease from healthy controls to that in more advanced stages of T2D [18]. Interestingly, Pellitero et al reported circulating METRNL levels before and after laparoscopic sleeve gastrectomy (another bariatric surgery technique).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Article Thieme ic individuals [19]. Other studies reported lower METRNL concentration in patients with T2D with a gradual decrease from healthy controls to that in more advanced stages of T2D [18]. Interestingly, Pellitero et al reported circulating METRNL levels before and after laparoscopic sleeve gastrectomy (another bariatric surgery technique).…”
Section: Discussionmentioning
confidence: 99%
“…METNRL was also found to be related to the browning of white fat depots and improved glucose tolerance in obese/diabetic mice [16,17]. However, data on circulating METNRL concentration in subjects with T2D are conflicting [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with stable angina pectoris and atrial fibrillation in stable disease, ELA levels will be reduced (Cui et al, 2021;Diakowska et al, 2021). Further, compared with healthy people, serum ELA is lower in patients with diabetic nephropathy (Onalan et al, 2020). In patients with CKD, the serum ELA level gradually decreases with the reduced GFR level, with the lowest values observed in patients with CKD5 (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same research group has documented that increased Metrnl plasma concentration resulted in increased EE, and improved glucose tolerance and anti-inflammatory cytokines [ 336 ]. In addition, the plasma Metrnl level has been reported to be lower in people with T2D [ 340 ] and osteoarthritis [ 341 ] when compared to healthy subjects. On the other hand, some research reported a higher level of Metrnl in individuals with obesity [ 342 ], and a positive association of Metrnl with BMI, waist circumference, total cholesterol, triglyceride, and low-density lipoprotein cholesterol in individuals with T2D [ 342 , 343 ].…”
Section: Cytokines That Burn Our Fire: Are They the Cornerstones Of Obesity Treatment For The Foreseeable Future?mentioning
confidence: 99%